Origin of micrometer-sized impact diamonds in ureilites by catalytic growth involving Fe-Ni-silicide: The example of Kenna meteorite. (15th September 2021) - Barbaro, Anna; Domeneghetti, Maria Chiara; Litasov, Konstantin D.; Ferrière, Ludovic; Pittarello, Lidia; Christ, Oliver; Lorenzon, Sofia; Alvaro, Matteo; Nestola, Fabrizio
Abstract: The occurrence of shock-induced diamonds in ureilite meteorites is common and is used to constrain the history of the ureilite parent bodies. We have investigated a fragment of the Kenna ureilite by micro-X-ray diffraction, micro-Raman spectroscopy and scanning electron microscopy to characterize its carbon phases. In addition to olivine and pigeonite, within the carbon-bearing areas, we identified microdiamonds (up to about 10 μm in size), nanographite and magnetite. The shock features observed in the silicate minerals and the presence of microdiamonds and nanographite indicate that Kenna underwent a shock event with a peak pressure of at least 15 GPa. Temperatures estimated using a graphite geothermometer are close to 1180 °C. Thus, Kenna is a medium-shocked ureilite, yet it contains microdiamonds, which are typically found in highly shocked carbon-bearing meteorites, instead of the more common nanodiamonds. This can be explained by a relatively long shock event duration (in the order of 4–5 s) and/or by the catalytic effect of Fe-Ni alloys known to favour the crystallization of diamonds. For the first time in a ureilite, carletonmooreite with formula Ni3 Si and grain size near 4–7 nm, was found. The presence of nanocrystalline carletonmooreite provides further evidence to support the hypothesis of the catalytic involvement of Fe-Ni bearing phases into the growth process of diamond from graphite during shock events in the ureilite parent body, enabling the formation of micrometer-sized diamond crystals.